2014
DOI: 10.3109/00016357.2014.939710
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of surface roughness and bond strength of quartz fiber posts after various pre-treatments

Abstract: Sandblasting or Er:YAG laser-irradiation of the surface of the quartz fiber post before cementation is recommended for increasing retention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 29 publications
1
19
0
1
Order By: Relevance
“…[35] An another study reveals that sandblasting and Er:YAG laser irradiation of the surface of the quartz fiber post before cementation provided a significant increase in bond strength between quartz fiber posts and resin cement. [36] Arslan et al [16] investigated the effects of Er:YAG laser irradiation at different parameters and the sandblasting method on the push-out bond strength of FRC posts to composite resin cores. For artificial aging, the specimens were subjected to thermal cycling.…”
Section: Discussionmentioning
confidence: 99%
“…[35] An another study reveals that sandblasting and Er:YAG laser irradiation of the surface of the quartz fiber post before cementation provided a significant increase in bond strength between quartz fiber posts and resin cement. [36] Arslan et al [16] investigated the effects of Er:YAG laser irradiation at different parameters and the sandblasting method on the push-out bond strength of FRC posts to composite resin cores. For artificial aging, the specimens were subjected to thermal cycling.…”
Section: Discussionmentioning
confidence: 99%
“…Akin et al evaluated the bond strength of quartz fiber posts after different surface treatment methods and reported the highest bond strength in the sandblasted followed by the Er:YAG laser irradiated groups; these two methods significantly increased the bond strength of quartz fiber posts to resin cement. 35 Moreover, Kriznar et al evaluated the micro-push-out bond strength of Multicore Flow resin material to 2 types of fiber posts following Er:YAG laser irradiation, and showed that Er:YAG laser irradiation negatively affected the bond strength of resin material to fiber posts. 16 Controversial results of different studies may be attributed to factors such as type of fiber post and differences in laser parameters.…”
Section: Discussionmentioning
confidence: 99%
“…26,40 Literatürde ve klinik pratiğinde çokça çalışılmış ve halen araştırılmaya devam eden en iyi en popüler teknik kumlamadır. [41][42][43][44][45] Çeşitli çalışmalar, farklı alüminyum oksit partikül boyutları ile (25-250 µm) kum-…”
Section: Tepeklinikunclassified